MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MEMBENTUK MENGGUNAKAN MEDIA TANAH LIAT DI KELOMPOK B TK AR-ROFI (Penelitian Tindakan Kelas di Kelompok B TK Ar-Rofi Bantargebang-Bekasi) - Iin Samsiah Nurfajria (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
The purpose of this research is to (1) to know the initial state of fine motor of the child, (2) to know the learning process in applying the activity forming using clay media, (3) and to know the fine motor ability of the child through group B activity in Ar- Bantargebang Bekasi. The type of this research is Classroom Action Research (PTK) consisting of two cycles, each cycle consisting of 8 actions, but for cycle II only used 4 times action just to find more valid data again. The subjects were 13 children of group B (aged 5-6 years) at Ar-Rofi Bantargebang Bekasi kindergarten consisting of 8 girls and 5 boys. Method of completion of data is done through observation, interview and documentation. Data analysis technique is done qualitatively and quantitatively, for success indicator in this research is 70%. The ability that passes the child changes after being given the action. Children have started to coordinate the movement of the eyes and hands and fingers in every activity. For that can be drawn conclusions have been successful.